Planejamento: um instrumento de possibilidades na cultura da escola? - Casagrande, Suellen Beatriz Martins (2014)
This study investigates how Planning is understood in the culture of the school, considering the perceptions of nine teachers and a manager of an elementary school (Fundamental I) from a private school in São Paulo, searching for the improving of the practice of these professionals and the teaching-learning process. The paper presents a theoretical exploration of Planning and school culture from a selection of authors whose proposals are linked to the educational environment. This enables the understanding of different levels, their roles, objectives and use for the contribution and the development of pedagogical work and teaching-learning process. Then, the concepts of culture of some authors on issues relating to school context, organization, identity and attachment to Planning are reviewd. Documentary analysis of different Plannings of the school researched make possible to establish relationships between theory, research context and practice, joined to the use of questionnaire and semi structured interviews. Results indicate the importance of planning as a tool that offers significant possibilities for the educator to work and to the educational institution, as well the contribution to the quality of teaching-learning process and success in school development